2020
DOI: 10.1177/2473974x20957975
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta‐analysis of Smell and Taste Disorders in COVID‐19

Abstract: Objective Loss of smell and taste are considered potential discriminatory symptoms indicating triaging for coronavirus disease 2019 (COVID-19) and early case identification. However, the estimated prevalence essential to guide public health policy varies in published literature. This meta-analysis aimed to estimate prevalence of smell and taste loss among COVID-19 patients. Data Sources We conducted systematic searches of PubMed, Embase, Web of Science, and Google Scholar databases for studies published on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 58 publications
6
66
0
2
Order By: Relevance
“…This highlights the importance of including data from community-dwelling individuals with COVID-19 in addition to routine hospital reports as hospital reports are less likely to capture mild signs and symptoms that might be important for early detection of disease. Loss of smell or taste was reported in less than 10% of individuals with DS, which was similar to the numbers reported in individuals without DS from the ISARIC4C survey, but much lower than the prevalence reported by other studies (48% loss of smell and 41% loss of taste as summarized in reference [27] ). The most likely explanation for these differences to more recent studies is that most T21RS and ISARIC4C cases were reported during the first wave of the pandemic, when we had very little knowledge about the variety of COVID-19 symptoms leading to an underdiagnosis of smell and taste disorders.…”
Section: Discussionsupporting
confidence: 79%
“…This highlights the importance of including data from community-dwelling individuals with COVID-19 in addition to routine hospital reports as hospital reports are less likely to capture mild signs and symptoms that might be important for early detection of disease. Loss of smell or taste was reported in less than 10% of individuals with DS, which was similar to the numbers reported in individuals without DS from the ISARIC4C survey, but much lower than the prevalence reported by other studies (48% loss of smell and 41% loss of taste as summarized in reference [27] ). The most likely explanation for these differences to more recent studies is that most T21RS and ISARIC4C cases were reported during the first wave of the pandemic, when we had very little knowledge about the variety of COVID-19 symptoms leading to an underdiagnosis of smell and taste disorders.…”
Section: Discussionsupporting
confidence: 79%
“…Recently more symptoms are being reported like loss of smell and taste sensation (132). A meta-analysis of 27 studies showed a pooled prevalence of loss of smell and taste in these patients to be 41.47% (95% Cl 3.13-31.03%) and 35.04% (95% Cl 22.03-49.26%), respectively (133). Both of these symptoms presented in patients on average on the fourth day after initial symptoms of the disease, but 13-15.5% of patients had a loss of smell and taste sensation as the first symptom (134,135).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…This patient had typical symptoms of COVID-19 that included fever, taste impairment, whole body pains, and severe breathing difficulties during 15 days since the symptom onset. The prevalence of smell and taste loss among COVID-19 patients has been found to be high globally (41% to 48%); hence health workers must consider the loss of smell and taste as suspicion indices for empirical diagnosis of SARS-CoV-2 infection 9,10 . In this case report, the patient's featured symptoms supported the diagnosis of a severe COVID-19 condition.…”
Section: Discussionmentioning
confidence: 99%